Immune checkpoint inhibitors: therapeutic advances in melanoma - Márquez-Rodas, Ivan; Cerezuela, Pablo; Soria, Ainara; Berrocal, Alfonso; Riso, Aldo; González-Cao, María; Martín-Algarra, Salvador (Annals of Translational Medicine; Vol 3, No 18 (October 30, 2015): Annals of Translational Medicine (Focus on “Melanoma”), 2015)
In recent years, new strategies for treating melanoma have been introduced, improving the outlook for this challenging disease. One of the most important advances has been the development of immunotherapy. The better understanding of the role of the immunological system in tumor control has paved the way for strategies to enhance the immune response against cancer cells. Monoclonal antibodies (mAbs) against the immune checkpoints cytotoxic T-lymphocyte antigen-4 (CTLA-4) and programmed cell death protein 1 (PD-1) and its ligand (PD-L1) have demonstrated high activity in melanoma and other tumors. Ipilimumab, an anti CTLA-4 antibody, was the first drug of this class that was approved. Although the response rate with ipilimumab is low (less than 20% of patients have objective responses), 20% of patients have long survival, with similar results in the first and second line settings. Nivolumab and pembrolizumab, both anti PD-1 inhibitors, have been approved for the treatment of melanoma, with response rates of 40% and a demonstrated survival advantage in phase III trials. This has marked a new era in the treatment of metastatic melanoma and much research is now ongoing with other drugs targeting checkpoint inhibitors. In addition, the agonist of activating molecules on T cells and their combinations are being investigated. Herein we review the clinical development of checkpoint inhibitors and their approval for treatment of metastatic melanoma.